Idea Poll - Camps, Yaiza; Grunke, Moritz; Pichler, Michalis (Conceptual Poetics Day; Miss Read, 2021)
IDEA POLL collected ideas regarding publishing activities and beyond. IDEA POLL 2020/21 was created through an online query and features about 100 responses from diverse international networks.
English
Keywords: N400-3990 Art museums, galleries, etc; Publishing